Stereoselective synthesis of alicyclic ketones: a hydrogen borrowing approach - Armstrong, RJ; Akhtar, WM; Frost, JR; Christensen, KE; Stevenson, NG; Donohoe, TJ (Elsevier, 2019)
A highly diastereoselective annulation strategy for the synthesis of alicyclic ketones from diols and pentamethylacetophenone is described. This process is mediated by a commercially available iridium(III) catalyst, and provides efficient access to a wide range of cyclopentane and cyclohexane products with high levels of stereoselectivity. The origins of diastereoselectivity in the annulation reaction have been explored by a series of control experiments, which provides an explanation for how each stereocentre around the newly forged ring is controlled.